Mass Transfer and Colour Analysis during Vacuum Frying of Colombian Coastal Carimañola - Angie D. Caro C; Sandrith P. Sampayo R; Diofanor Acevedo C; Piedad Montero C; Raúl J. Martelo (International Journal of Food Science)
This study is aimed at analysing the effect of vacuum frying on the kinetic parameters of mass transfer, the CIE L∗a∗b∗ colour parameters of the Carimañola. For the kinetic analysis, the moisture and oil content were measured by means of an experimental design consisting of two factors: frying time with seven levels (60, 120, 180, 240, 300, 420, and 540 s) and frying temperature with three levels (120, 130, and 140°C). The diffusivity coefficient, the moisture transfer rate, and the oil adsorption rate, with their respective activation energies, were calculated. For the colour analysis, the reflectance technique was used to determine the colour coordinates of the CIE L∗a∗b∗ space, and the general colour change was calculated (ΔE). Concerning the kinetics, the increase in temperature and frying time reduced the moisture content, while the oil content decreased with the increase in temperature and increases with frying time. The diffusivity ranged from 1,238×10−6 m2/s at 120°C to 2,84×10−6 m2/s at 140°C. The mass transfer coefficients for moisture ranged from 2×10−4 m/s at 120°C to 4×10−4 m/s at 140°C. The values of the oil uptake rate were from 0.0022 s-1 at 120°C to 0.0018 s-1 at 140°C. Finally, the luminosity parameter shows a decrease with the increase in temperature, although the first 240 s shows a rise and then begins to decrease. Vacuum frying allowed Carimañolas to be obtained with a lower oil and moisture content, with an appropriate colouring, eye-catching and visually attractive to consumers.